Sustainable energy and environment : an earth system approach - Kundu, Sandeep Narayan, 1974-; Nawaz, Muhammad, 1966- (Oakville, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2020)
Here is a comprehensive introductory discussion of Earth, energy, and the environment in an integrated manner that will lead to an appreciation of our complex planet. The book looks at Earth from the perspective of a livable planet and elaborates on the surface and subsurface processes and the various energy cycles where energy is transformed and stored in the planet's various spheres. The chapters discuss the interactions between the different parts of Earth--how energy is exchanged between the atmosphere, hydrosphere, biosphere, and geosphere, and how they impact the environment in which we live.
OCLC-licensed vendor bibliographic record.
Keywords: Renewable energy sources -- Environmental aspects; BUSINESS & ECONOMICS / Industries / Energy Industries; SCIENCE / General; SCIENCE / Earth Sciences / General